Compulsory schooling and geographic distribution on voluntary education - Alpay Filiztekin; Can Karahasan (European Regional Science Association (ERSA), 2015)
Compulsory schooling increases average level of education in a country and provides other benefits, its effect on geographical distribution is, however, not obvious. We explore the effect of a sudden change in compulsory schooling in Turkey, that increased mandatory years of schooling from five to eight years, on spatial distribution of educational attainment. Using data on two cohorts, the cohort that had affected by the change and the immediate cohort that had not, we show that an increase in the dispersion of the shares of people with voluntary education across space. We find that that an increase in years of compulsory schooling makes local conditions that already generate heterogeneity more important to shape the distribution.
Keywords: I21; I24; J24; R12; 330